Gravitation near the Schwarzschild radius - L. Khokhlov, D. (International Journal of Advanced Astronomy, 2021)
The problem of gravitation near the Schwarzschild radius is addressed. The pressure due to free fall velocity is introduced. At the Schwarz-schild radius, this pressure produces the force balancing the gravity thus stopping the collapse of the matter. The minimum radius of the source of gravity is defined as a radius at which the proton reaches the Planck energy. The compact object as a thin shell at the minimum radius is considered. The proton is assumed to decay at the Planck scale into positron and hypothetical Planck neutrinos. Under accretion onto the compact object, half the protons decay, and the other protons retain at the minimum radius.Â Â
Keywords: Compact Object; Free Fall Pressure; Gravitation; Proton Decay; Schwarzschild Radius.